Effect of evaporative weathering and oil-sediment interactions on the fate and behavior of diluted bitumen in marine environments. Part 1. Spill-related properties, oil buoyancy, and oil-particulate aggregates characterization. (January 2018) - Hua, Yujuan; Mirnaghi, Fatemeh S.; Yang, Zeyu; Hollebone, Bruce P.; Brown, Carl E.
Abstract: The fate and behavior of diluted bitumen spilled in marine conditions has recently become a topic of much interest, yet, only limited knowledge is available. One of the major issues of a diluted bitumen spill on water is whether the product will sink, especially when suspended sediment is present in the water column. This study demonstrated how weathering processes influenced the key spill-related properties of a diluted bitumen product (Cold Lake Blend-Winter), and how interaction of diluted bitumen with sediment affected its tendency to float or sink in water. This study showed that the weathering states of the oils as well as the size of sediment are important factors influencing oil-sediment interactions and the tendency of the formed oil-particulate aggregates for buoyancy. When mixing with fine- and medium-sized sediments, the fresh to moderately weathered oils formed oil-particulate aggregates and sank in saltwater, while the very heavily-weathered oil formed discrete free-floating tarballs. Graphical abstract: Image 1 Highlights: The fate and behavior of spilled diluted bitumen in the marine environment were studied. The interactions of fresh and weathered sates of diluted bitumen with three types of sediments were evaluated. The physical properties of the oil-particulate aggregates (density, morphology, particle size and buoyancy) were evaluated.